2018
DOI: 10.1177/0020872818808352
|View full text |Cite
|
Sign up to set email alerts
|

African refugee spouses’ experience of resettlement in regional Australia: Disempowering and empowering narratives

Abstract: This study examined the experiences of eight African refugees resettled in regional Australia. Informed by the notion/idea of intersectionality and others, this study utilised interviews to capture the role of gender, culture, contextual realities of Australia and the participants’ family relations to analyse experiences of gender conflict. The study found that among other things, financial pressures, self-development and differences in power relations contributed to conflict and sometimes separation of couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…This study indicated that most skilled African migrant parents in this study were successfully managing the tensions of raising children in complicated transnational, multicultural and intercultural environments and showed a willingness to temper and adapt their parenting styles accordingly. In contrast to other studies (e.g., Kuyini & Kivunja, 2018; Okeke‐Ihejirika & Salami, 2018), couples in this study appeared to be navigating changes in their family dynamics without high levels of marital discord. Our research therefore suggests an alternative narrative that indicates that contrary to the dominant representations of African migrant families that report high levels of conflict and violence following relocation, the skilled African migrant families involved in this study were able to successfully adapt and change their behaviour and attitudes leading to new family dynamics, which strengthened parental and marital relationships.…”
Section: Resultscontrasting
confidence: 99%
“…This study indicated that most skilled African migrant parents in this study were successfully managing the tensions of raising children in complicated transnational, multicultural and intercultural environments and showed a willingness to temper and adapt their parenting styles accordingly. In contrast to other studies (e.g., Kuyini & Kivunja, 2018; Okeke‐Ihejirika & Salami, 2018), couples in this study appeared to be navigating changes in their family dynamics without high levels of marital discord. Our research therefore suggests an alternative narrative that indicates that contrary to the dominant representations of African migrant families that report high levels of conflict and violence following relocation, the skilled African migrant families involved in this study were able to successfully adapt and change their behaviour and attitudes leading to new family dynamics, which strengthened parental and marital relationships.…”
Section: Resultscontrasting
confidence: 99%
“…The resettlement experiences of African migrants in Australia may differ from one state to another. African migrants may experience difficulties when trying to adjust to their host state and can face racism, unemployment, financial constraints, gender and role reversal, which may lead to a breakdown of couples or families and can cause mental health problems (Abur and Spaaij 2016, Abur 2018, Kuyini and Kivunja 2018. Ogunsiji et al (2012) also reported that African women were exposed to risk factors, including under-and unemployment, and being forced to 'start again', which affected their mental health.…”
Section: Experiences Of Migrants In Australiamentioning
confidence: 99%
“…D Hack-Polay [ 57 ] views self-and external categorisations as the main factors that support the management of identities, which cause contradictions in the behaviours of the subjects who seek new identities. The research examined the way in which the forced migrants steer multiple identities [ 40 ], which often signified the discarding or suspension of a certain identity in favour of more beneficial ones was transactional and situated. The findings support the view that identities are not bicultural but far more complex and relational- including differences between migrants, refugees and those settled for longer or shorter time periods [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method was most suitable for this research because thematic analysis helps ‘interrogate the various meanings that subjects attach to phenomena’ [ 48 , 49 ]. As pointed out by AB Kuyini and C Kivunja, ‘moving to another country is associated with loss at different levels, and issues of identity, power/influence and knowledge habitus are all at play [ 40 ]. These issues tend to be exacerbated when such migrations are forced, as in the case of the forced migrants interviewed in this research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation